HUBUNGAN TINGKAT STRES DENGAN TINGKAT DYSMENORRHOEA PADA SISWI KELAS X DAN XI SMK BHAKTI KARYAKOTA MAGELANG TAHUN 2014 - Hidayah Hisham Saleh Salim; Bekti Yuniyanti (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2015)
Prevalence rate of menstruation pain is about 45-95% in productive women. This problem interferes 50% reproductive women and 60-85% teenager causing much absence on school and office. Commonly, among 50-60% women need analgetic to overcome this problem (Annathayakheisha, 2009 in Sukini dkk, 2012).This research aims to know the correlation between stress level with dysmenorrhoea level on students of grade X and IX of SMK Bhakti Karya Magelang City year 2014.The type of this research is correlative analytic using cross sectional design and accidental sampling. The samples taken are students of grade X and XI who undergo dysmenorrhoea and meet the inclusion and exsclusion requirements, those 138 students. The data is taken between April 1 and April 30, 2014 applying quetionaire as its instrument.The result shows that more respondents are said to be normal and have light dysmenorrhoea, those are 15 respondents (55,6%), while more respondents who undergo very heavy stress feel heavy dysmenorrhoea, those are 3 students (60,0%). Kendall’s Tau test result that is computerized analysis shows 0,344 in t number. So, the conclusion is that there is positive correlation between stress level with dysmenorrhoea level on students of grade X and XI of SMK Bhakti Karya Magelang City year 2014.Hopefully, students who undergo dysmenorrhoea will increase the knowledge about the cause of dysmenorrhea and its management especially considering psychological condition. Besides, institution, particularly conselling teacher is hoped to give consultation for students for managing and preventing stress on teenagers to avoid the health disturbance especially reproduction health.